Bovine tuberculosis model validation against a field study of badger vaccination with selective culling - Graham C. Smith; Richard Budgey (PLoS ONE, 2025)
Bovine tuberculosis (bTB) is a costly disease in Britain and Ireland shared by cattle and badgers ( Meles meles ), and to reduce the infection in cattle to low levels some form of badger management is considered necessary. We compare the results of a badger field trial where test-positive badgers are culled, and test-negative badgers vaccinated (a TVR approach) with the results of the simulation model originally used to predict the effect of the trial in Northern Ireland. Initial model results depended strongly on whether social perturbation occurred in the badger population following culling, and the field study demonstrated no evidence for such behavior. Here we re-run the model with the initial conditions of the TVR study and with no social perturbation and predict a similar outcome in terms of number of badgers caught, number testing positive, and the substantial decline in prevalence. These results validate our model and demonstrate the utility of such predictive modelling for this disease system. This is particularly important as the UK government moves away from widespread badger culling in England toward more vaccination, as this combined approach of vaccination and selective culling based on test results may give a more robust method of disease management than just vaccination on its own.